Dynamic regulation of canonical TGFβ signalling by endothelial transcription factor ERG protects from liver fibrogenesis. Issue 1 (December 2017) - Dufton, Neil; Peghaire, Claire; Osuna-Almagro, Lourdes; Raimondi, Claudio; Kalna, Viktoria; Chuahan, Abhishek; Webb, Gwilym; Yang, Youwen; Birdsey, Graeme; Lalor, Patricia; Mason, Justin; Adams, David H.; et al.
Abstract The role of the endothelium in protecting from chronic liver disease and TGFβ-mediated fibrosis remains unclear. Here we describe how the endothelial transcription factor ETS-related gene (ERG) promotes liver homoeostasis by controlling canonical TGFβ-SMAD signalling, driving the SMAD1 pathway while repressing SMAD3 activity. Molecular analysis shows that ERG binds to SMAD3, restricting its access to DNA. Ablation of ERG expression results in endothelial-to-mesenchymal transition (EndMT) and spontaneous liver fibrogenesis in EC-specific constitutive hemi-deficient (Erg cEC-Het ) and inducible homozygous deficient mice (Erg iEC-KO ), in a SMAD3-dependent manner. Acute administration of the TNF-α inhibitor etanercept inhibits carbon tetrachloride (CCL4 )-induced fibrogenesis in an ERG-dependent manner in mice. Decreased ERG expression also correlates with EndMT in tissues from patients with end-stage liver fibrosis. These studies identify a pathogenic mechanism where loss of ERG causes endothelial-dependent liver fibrogenesis via regulation of SMAD2/3. Moreover, ERG represents a promising candidate biomarker for assessing EndMT in liver disease. The transcription factor ERG is key to endothelial lineage specification and vascular homeostasis. Here the authors show that ERG balances TGFβ signalling through the SMAD1 and SMAD3 pathways, protecting the endothelium from endothelial-to-mesenchymal transition and consequent liver fibrosis in mice via a SMAD3-dependent mechanism.